Logging concessions, certification & protected areas in the Peruvian Amazon: Forest impacts from combinations of development rights & land-use restrictions - Jimena Rico; Stephanie Panlasigui; Colby J. Loucks; Jennifer Swenson; Alexander S. P. Pfaff (Banco de México, 2018)
In this paper, we use geospatial data and difference-in-differences models to identify the deforestation effects, during 2000-2013, of the leading forest policies in the Peruvian Amazon: i) logging concessions, ii) third-party certification of concessions, and iii) Protected Areas (PAs). We find that on average logging concessions have no effect on tree-cover loss, while the PAs do reduce loss. Further, the PAs allowing limited private extraction save more forest than do more restrictive PAs. Certification has an impact (reduces loss) only in the single region where concessions reduce loss, suggesting a complementarity of third parties with private and public efforts to govern concessions. Our results suggest roles for private rights within conservation, given oversight.
Keywords: Q23; Q56; Q24; O13; 330; certification; FSC; deforestation; concessions; protected areas; impact evaluation